Sprint and Anaerobic Power with the Soccer-Specific ACTN3 Gene: A Distintive Example - TACAL ASLAN, BESTE; POLAT, TOLGA; YILMAZ, ÖZLEM ÖZGE; ULUCAN, KORKUT (My University, 2024)
The aim of this study is twofold: (1) to identify differences in certain anaerobic parameters (10m sprint, 30m sprint, anaerobic power, and Illinois agility tests) between professional and amateur soccer players, and (2) to determine whether there is a difference in theACTN3gene polymorphism between professional and amateur soccer players. Ultimately, the goal is to reveal which parameters contribute to the differentiation in these two aspects. A total of 133 volunteer soccer players, including 71 professionals and 62 amateurs, participated in the research. DNA extraction from buccal epithelial cells was performed using a commercial kit to determine the genetic background of the athletes, and Real-Time PCR was conducted for genotyping. Statistical analysis of the findings obtained from the test results was performed using the SPSS 23 (SPSS Inc., Chicago, IL, USA) package program. The homogeneity of variance of the data was assessed using the Levene Test, and normal distribution analyses were conducted using the Shapiro-Wilk Test. Chi-square and Mann-Whitney U tests were employed for parameter analysis. The significance level was set at p<0.05. Evaluation of the data in our study revealed no statistically significant difference inACTN3rs1815739 gene polymorphism between the groups (p>0.05). However, there is a statistically significant difference in anaerobic parameters (10m sprint, 30m sprint, and anaerobic power) except for the Illinois test (p<0.05). In conclusion, our study found that gene polymorphism is not a differentiating factor between professional and amateur soccer players, but speed (10m and 30m) and anaerobic power parameters are differentiating factors.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Endurance; Sport Genetics; Polymorphism; Yo-Yo IRT1